Mathematical modelling of aerodynamic characteristics for flapping wing ornithopter - Ramli, Alif Syamim Syazwan (2015)
Natural cycle and creation has led to some really efficient flying creatures. It is important to look at the criteria, characteristic and constraints in order to understand how the mechanisms, principles and natural design are aerodynamically achieved. The objective of this study is to establish the salient features and functional implication from various components characterized from the dynamics, kinematics, and aerodynamics of the flying biosystems, and to synthesize a simple yet comprehensive workable mathematical aerodynamic modelling of flapping wing ornithopter. Considerations are given to the motion of a three-dimensional thin rigid wing in flapping and pitching motion with phase lag. Fundamental unsteady aerodynamic analytical approach using modified strip theory incorporating leading-edge suction and viscous effect is utilized for modelling development. The two-dimensional computational fluid dynamic simulation procedure is done on heaving thin rigid wing using ANSYS-CFX software for validation purpose. For the analytical computation, the first part of the study is focused on a bi-wing ornithopter. Parametric study is carried out to reveal the flapping bi-wing ornithopter aerodynamic characteristics and for comparative analysis with various selected simple models in the literature. Further analysis is carried out by differentiating the pitching and flapping motion and studying its respective contribution to the flight forces. Similar procedure is then applied to flapping quad-wing ornithopter model. The present flapping wing aerodynamic model results computed have been validated satisfactorily with other relevant comparable studies. The analysis of component-wise contribution based on the flapping and pitching motion shows that: (a) The lift is influenced mostly by the incidence angle (b) The thrust is influenced mostly by flapping motion (c) Phase-lag could be utilized to obtain optimum lift and thrust for each wing configurations. For the quad-wing ornithopter at the present stage, the simplified computational model adopted has verified the gain in force obtained as compared to bi-wing flapping ornithopter. All these results which have been satisfactorily validated lend support to the generic modelling development adopted for the synthesis of flight model. It is also capable to reveal basic characteristics of flapping wing ornithopter that is useful for optimization of geometry, kinematics and aerodynamics design of flapping wing mechanization.